2006
DOI: 10.1111/j.1742-7843.2006.pto_494.x
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Captopril on Nicotine‐Induced Endothelial Dysfunction in Rat

Abstract: This study was designed to examine the in vivo and in vitro effects of captopril, an angiotensin-converting enzyme inhibitor, on nicotine-induced endothelial dysfunction in rats. Endothelial dysfunction was induced by exposing isolated rat mesenteric arteries to nicotine (0.01, 0.1, or 1 mM) for 24 hr using an organ culture system, or by treating rats with nicotine (2 mg/kg/day, intraperitoneally) for 4 weeks. The protective effects of captopril were tested by exposing isolated mesenteric arteries to captopril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…At the end of the equilibration period, the contractile capacity of each ring was tested by exposure to a high-K þ Krebs' solution (obtained by equimolar replacement of NaCl by KCl in the Krebs' solution), and the ring was considered viable and used for experiments only if two reproducible high-K þ contractions were obtained. 20,22 Vascular Reactivity Studies Endothelium-dependent and -independent relaxations were assessed by measuring the dilatory responses of mesenteric arteries to cumulative concentrations of acetylcholine (ACh; 10 À 10 -10 À 5 mol/l) and sodium nitroprusside (SNP; 10 À 10 -10 À 5 mol/l), respectively. All experiments were performed in vessels pre-contracted with phenylephrine (PE; 10 mmol/l).…”
Section: Mesenteric Artery Preparation and Isometric Tension Measurementmentioning
confidence: 99%
“…At the end of the equilibration period, the contractile capacity of each ring was tested by exposure to a high-K þ Krebs' solution (obtained by equimolar replacement of NaCl by KCl in the Krebs' solution), and the ring was considered viable and used for experiments only if two reproducible high-K þ contractions were obtained. 20,22 Vascular Reactivity Studies Endothelium-dependent and -independent relaxations were assessed by measuring the dilatory responses of mesenteric arteries to cumulative concentrations of acetylcholine (ACh; 10 À 10 -10 À 5 mol/l) and sodium nitroprusside (SNP; 10 À 10 -10 À 5 mol/l), respectively. All experiments were performed in vessels pre-contracted with phenylephrine (PE; 10 mmol/l).…”
Section: Mesenteric Artery Preparation and Isometric Tension Measurementmentioning
confidence: 99%
“…Nicotine has been noted to increase generation of superoxide by activation of NADPH oxidase and PKC, which ultimately damages the kidney [23,31,58] . The destructive role of PKC is manifested as inhibition of PKC by calphostin C, a potent PKC inhibitor, which prevents nicotine-induced mesangial cell proliferation and fibronectin production.…”
Section: Participation Of Smoking Mediated Oxidative Stress In the Dementioning
confidence: 99%
“…6,11 Inflammation has an important role in the process of atherosclerosis plaque growth until thrombosis occurs that is caused by rupture. 9,25,26 Macrophage located in the plaque contributes to the atherosclerosis occurrence by activating NF-κB to stimulate proinflammatory genes production. 5 Release of proinflammatory cytokines such as IL-6, IL-1, and TNF-α shows the main regulators from CRP, thus CRP concentration in the body stand for the indicator of a non specific systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with previous study which showed that nicotine induction at dose of 2 mg/kg BW cause endothelial dysfunction as indicated by the increase of serum CRP concentation. 5,6,26,27 Nicotine stimulates the production of the inflammatory mediators such as IL-6, IL-1 and TNF-α as main regulator of CRP. Moreover, nicotine induces of CRP production of macrophage by activating the transcription factor NF-κB.…”
mentioning
confidence: 99%